Beyond Garment - Farren, Anne (Western Australian Museum, 2010)
To reflect on the exhibition, four essays have been penned by Anne Farren, Ann Schilo, Christiane Keller and Kirsten Hudson. These essays examine the concepts that lay behind Beyond Garment, and explore the meaning of fashion and materials from a variety of viewpoints.